Gorgias' apatē, Sophocles' Electra, and cognitive criticism - Grethlein, Jonas (Minds on stage, 2023)
This chapter offers a fresh look at the false messenger scene in Sophocles’ Electra through the combined lenses of ancient criticism and cognitive studies. In a first step, it contends that the claims of Gorgias fr. B 23 DK correspond with insights of cognitive accounts of aesthetic experience. In its main part, the chapter reconsiders Electra in the light of Gorgias fr. B 23 DK, suggesting that the false messenger speech stages the entwinement of deception with aesthetic illusion with which Gorgias fr. B 23 DK plays. It is first shown that the messenger speech is geared towards generating a strong aesthetic illusion. Then it is argued that the very devices that serve to engross the theatre audience are simultaneously a means of deception within the play. As pointed out in the conclusion, this association of aesthetics with ethics reveals a specifically ancient approach and sheds light on the limits as well as the benefits of employing cognitive studies in classics.